Media Pembelajaran Tari Tepak Keraton Sebagai Upaya Pelestarian Budaya Palembang - Rosalia; Bobby Halim; Didiek Prasetya (Besaung : Jurnal Seni Desain dan Budaya, 2026)
Tari Tepak Keraton is one of the intangible cultural heritages originating from Palembang, Sumatera Selatan, which holds high historical, philosophical, and aesthetic values. However, it faces challenges in terms of regeneration, low interest among younger generations, and the lack of engaging and easily understandable learning media. This project aims to design and introduce a visual communication–based learning medium through an educational video of Tari Tepak Keraton for elementary school students aged 9–12 years in Palembang. The method used in this design process is the Design Thinking approach, which includes the stages of empathize, define, ideate, prototype, and test. Data were collected through observation, interviews, and literature studies related to culture and Visual Communication Design.The educational video is designed to be interactive and expressive, featuring clear and easily understandable narration, as well as a layout that represents the cultural character of Palembang. Through this learning medium, it is expected to enhance children’s understanding and interest in preserving Tari Tepak Keraton as a cultural identity of Palembang